Perceived parental bonding and cortisol awakening response in people with eating disorders. (August 2021) - Cascino, Giammarco; Marciello, Francesca; Monteleone, Alessio Maria; D'Agostino, Giulia; Patriciello, Giuseppina; Monteleone, Palmiero
Abstract: It is widely acknowledged that early life experiences may have an impact on hypothalamic–pituitary–adrenal (HPA) axis functioning in eating disorders (EDs). Parental bonding is defined as the parental contribution of care and control to parent–child relationships. We evaluated whether perceived care and protection of parental bonding in childhood and adolescence were associated with HPA axis functioning in adult patients with EDs. Sixty-four women with EDs participated in the study, 37 with anorexia nervosa and 27 with bulimia nervosa. Parental care and control (separately for the mother and father) were evaluated by the Parental Bonding Instrument. The activity of the HPA axis was assessed by measuring the salivary cortisol awakening response (CAR). Parental care and control did not differ significantly between the two diagnostic groups. High and low maternal care were associated with significantly different time patterns of CAR without any significant difference in the overall post-awakening production of cortisol. Maternal control, paternal care and paternal control were not associated with any difference in the CAR. Our results showed for the first time an association of perceived maternal care with the time pattern of CAR in female patients with EDs, while perceived parental control was not associated with any CAR feature. These findings support the idea that perceived characteristics of parental bonding in childhood and adolescence may influence the HPA axis activity in adults with EDs. Highlights: Parental care and control did not differ between eating disorder diagnostic groups. Maternal care was associated with different cortisol awakening response time pattern. Paternal care and control were not associated with the cortisol awakening response.